EXPRESSION OF OSTEOPONTIN IN ORAL SQUAMOUS CELL CARCINOMA – AN IMMUNOHISTOCHEMICAL STUDY - Alamgeer, Rabia; Khan, Muhammad Mumtaz; Nasir, Sabeen; Ahmad, Sajjad; Khurshid, Arooj; Saeed, Saleha (Journal of Postgraduate Medical Institute, 2023)
Objectives: To analyze the expression of Osteopontin (OPN) is well differentiated, moderately differentiated, and poorly differentiated oral squamous cell carcinoma (OSCC). Methodology: This study was conducted at the Department of Pathology, Peshawar Medical College, over a period of 12 months. A total of 50 formalin-fixed paraffin-embedded (FFPE) blocks (n=50) of confirmed cases with varying grades of OSCC were included in the study. Immunostaining was evaluated for intensity and percentage of positive cells and Immunoreactivity of OPN was assessed by the Immunoreactivity scoring system (IRS) method. Results: The age of the patients was 58.44 ± 13.01 years ranging from 30 to 82 years on average. Maximum number of cases belonged to the age group 51 to 70 years having 27 (54%) participants. The most common category of OPN expression among well differentiated OSCC was moderate (n=16, 66.7%). For poorly differentiated OSCC the strong staining was found in 6 cases (50%) and was the most common category of OPN expression. In males the pattern of staining for OPN expression was not statistically significant among various grades of OSCC (P=0.455) while among females the results were highly significant (P=0.003). The mean IHC staining score by IRS method for OPN expression was highest among well differentiated (9.20±4.31) Conclusion: OPN can be used as a diagnostic marker for OSCC. It can also help in assessing the potential aggressive behavior of the tumor pointing at close follow up of such patients for recurrence.